(Re) contextualizing the peripheral subjects: creative territories, media and visibility spaces - Martins, Rosana (2016)
This essay analyzes the theoretical articulation around the concepts of representation, sphere of visibility and social recognition, with the intention to portray the “peripheral cultural production”, its instances of production and distribution. The article seeks to identify the importance given to the conquest of space in terms of the peripheral groups visibility. It emerges in an increasingly permeated by a multifaceted range of circumscribed ambivalence in the metropolis, as a center for dissemination and use of social situation Culture in the context of a society marked by ruptures in the sense of human rationality brutalized by imaginary capital.